Pengaruh Komunikasi, Budaya Organisasi, Dan Kompetensi Terhadap Kinerja Karyawan Pada PT Menumbar Kaltim Samarinda - Tandi Kadang (E-BISMARK : Jurnal Ekonomi, Bisnis Dan Marketing, 2022)
The title of her research is the Influence of Communication, Organizational Culture, and Competence on Employee Work Performance at PT Menumbar Kaltim Samarinda,This research aims to determine the influence of communication, organizational culture, and competence on employee work performance at PT Menumbar Kaltim Samarinda.This research is catogorized as a survey research, where this instrument is using a questionnaire. The method of sampling in this research is Insidental Sampling, amounted to 30 respondent. The method of data analysis was carried out using multiple linear regression analysis using SPSS version 23 for windows.The results of this research indicate that communication, organizational culture and competence simultaneously have a significant effect on employee performance at PT Menumbar Kaltim Samarinda. From these three variables, it is known that Communication (X1) has a dominant effect compared to Competence (X3) and Organizational Culture (X2) on Employee Performance (Y). This can be seen from tcount where the tcount for the Communication variable (X1) is 0.482 which is greater than the Competence variable (X3) which is 0.466 and the Organizational Culture variable (X2) is 0.131.